Ontogeny of the hyoid apparatus in Jamaican fruit bats (Chiroptera: Phyllostomidae) in unraveling the evolution of echolocation in bats. (6th May 2019) - Carter, R. T.; Stuckey, A.; Adams, R. A.
Abstract: How echolocation and flight evolved in modern day bats is a compelling and largely unanswered question in biology. As laryngeal echolocation in bats is typified by a bony connection between the larynx and the auditory bulla via the hyoid apparatus, we developed an evolutionary‐developmental model of the hyoid to test hypotheses regarding the evolution of echolocation in bats. Using computed tomography of pre‐ and postnatal Jamaican fruit bats ( Artibeus jamaicensis ), we showed that much of the hyoid apparatus was ossified prior to parturition. This includes the stereotypical articulation of the stylohyal bone with the auditory bulla found in laryngeal echolocating bats, where the cranial end of the stylohyal is flattened and wraps around the auditory bulla. Postnatally, thyrohyal ossification coincided with the development of increased echolocation call emission rate and the development of flight. We contend that the stepwise development of the hyoid apparatus of A. jamaicensis presented here serves as a proxy for the series of transitional forms that lead to the modern day hyoid apparatus and its cranial articulation with the auditory bulla in modern day laryngeally echolocating bats. Abstract : As laryngeal echolocation in bats is typified by a bony connection between the larynx and the auditory bulla via the hyoid apparatus, we developed an evolutionary‐developmental model of the hyoid to test hypotheses regarding the evolution of echolocation in bats. The stereotypical articulation of the stylohyal bone with the auditory bulla occurred prenatally, while the final segments of the hyoid apparatus ossified postnatally and coincided with the latter stages of echolocation development. We contend that the step‐wise development of the hyoid apparatus presented here serves as a proxy for the transitional forms that lead to the modern‐day hyoid apparatus in laryngeally echolocating bats.